Evaluation of a hydrophilic interaction liquid chromatography design space for sugars and sugar alcohols - Hetrick, Evan M.; Kramer, Timothy T.; Risley, Donald S. (Journal of Chromatography A, 2017)
•A novel HILIC design space for analysis of sugars and sugar alcohols is described.•Aerosol detectors were used for the analysis of sugars and sugar alcohols.•A novel algorithm for analysis of design space data is presented.•Use of the algorithm for efficient method development is demonstrated.•Application for impurity control for pharmaceutical development is described. Based on a column-screening exercise, a column ranking system was developed for sample mixtures containing any combination of 26 sugar and sugar alcohol analytes using 16 polar stationary phases in the HILIC mode with acetonitrile/water or acetone/water mobile phases. Each analyte was evaluated on the HILIC columns with gradient elution and the subsequent chromatography data was compiled into a statistical software package where any subset of the analytes can be selected and the columns are then ranked by the greatest separation. Since these analytes lack chromophores, aerosol-based detectors, including an evaporative light scattering detector (ELSD) and a charged aerosol detector (CAD) were employed for qualitative and quantitative detection. Example qualitative applications are provided to illustrate the practicality and efficiency of this HILIC column ranking. Furthermore, the design-space approach was used as a starting point for a quantitative method for the trace analysis of glucose in trehalose samples in a complex matrix. Knowledge gained from evaluating the design-space led to rapid development of a capable method as demonstrated through validation of the following parameters: specificity, accuracy, precision, linearity, limit of quantitation, limit of detection, and range.